IMPLEMENTATION OF EFFECTIVE COMMUNICATION IN HEALTH EDUCATION ACTIVITIES FOR NON-COMMUNICABLE DISEASES TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Evert, Daniel Paulus; Suriaatmadja, Steffi Rifasa Tohir (TOPLAMA, 2024)
The world has a dream of achieving a prosperous society. This dream is encapsulated in the Sustainable Development Goals. One of the points included is Good Health and Well-being. A healthy society will lead to a developed and progressive nation. One of the obstacles to global health is non-communicable diseases. These diseases, which are among the leading causes of death worldwide, can be addressed early through prevention programs.  One such proven effective prevention program is health education. Health education is a form of communication to the community as a health effort. To achieve success, certain techniques are needed in the delivery process.  This study uses a qualitative method with a descriptive approach.  Data collection techniques were carried out through interviews and observations, while the data analysis techniques were data reduction, data modeling (data display), and concluding. The results of this study show that there are attitudes of Respect, Empathy, Audibility, Clarity, and humility (REACH) in the communication of general practitioners towards participants in health education activities conducted by Klinik Pratama Nuhato Antapani Bandung.